"“Stress”, “amnesia”, “può capitare a tutti”. Quando le parole non aiutano" "a comprendere" - Montanaro, Antonio (Il sogno della farfalla, 2019)
The aim of this article is to describe how Italian mass media depicts cases of children death caused by abandonment in the car. Specifically the author questions if the words used are able to clearly explain the causes leading to these tragic events. By analyzing the articles and comments published after the 7th June 2017, the day when a 18-months old child died due to hyperthermia, the author shows how journalists and academics tend to implicitly consider that these case could happen to any parent. They also usually believe that these events are determined by a temporary memory “blackout”, due to high stress level.Therefore the only preventive tool would be setting electronic sensor devices below children car seats. However, some experts affirm that the cultural and medical research should instead consider human relationships as an object of their studies. In other words, it would be more accurate to define this dynamic using the term of annulment pulsion or lack of affectivity. The author concludes emphasizing the importance of starting a research through a useful debate between the scientific community and the media workers also in relation to the terminology used.